Pengaruh Latihan Mindfulness Terhadap Penurunan Tekanan Darah Pada Ibu Preeklamsia Di Puskesmas Pajarakan Kabupaten Probolinggo - Dodik Hartono; Mariani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Preeclampsia is a collection of symptoms or syndromes that affect pregnant women over 20 weeks of gestation with the main signs being hypertension and proteinuria. Preeclampsia is a multisystem disorder that characteristically affects 2% - 5% of pregnancies and is one of the causes of most maternal and infant deaths. Several risk factors for preeclampsia are caused by maternal age, occupation, parity, gestational age, history of hypertension and education. Mothers who have many risk factors and previously suffered from preeclampsia have a 20% risk of experiencing preeclampsia. The aim of this research is to determine the effect of mindfulness training on reducing blood pressure in preeclamptic women at the Pajarakan Community Health Center, Probolinggo Regency. This research design uses pre-experimental using the one-group pre-post test design method. The total population was 30 respondents with a sampling technique using total sampling with a total of 30 research samples. The measuring tool uses mindfulness therapy SOPs and blood pressure observation sheets. The research results were processed with the help of SPSS 23 for Windows using the Wilcoxon statistical test. The results of the research: Blood pressure in preeclamptic mothers before being given mindfulness training was systolic blood pressure with a mean value of 148.53; median 147.50; SD 5,036; The minimum value is 141 and the maximum value is 159. Meanwhile, the diastolic blood pressure value is 137.77; median 138.00 ; SD 2,800 ; The minimum value is 130 and the maximum value is 142. Meanwhile, the blood pressure results in preeclamptic mothers after being given mindfulness training are systolic blood pressure with a mean value of 90.57; median 91.00 ; SD 3,954; The minimum value is 81 and the maximum value is 96. Meanwhile, the diastolic blood pressure value is 80.90; median 80.00 ; SD 3,680; The minimum score is 70 and the maximum score is 86. There is an effect of mindfulness training on reducing blood pressure in preeclamptic mothers at the Pajarakan Community Health Center, Probolinggo Regency with a value of ρ = 0.000 < α = 0.05.